2009
DOI: 10.1186/1472-6807-9-62
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hemagglutinin structural domain and polymorphisms which may modulate swine H1N1 interactions with human receptor

Abstract: Background: The novel A/H1N1 influenza virus, which recently emerged in North America is most closely related to North American H1N1/N2 swine viruses. Until the beginning of 2009, North American swine H1N1/N2 viruses have only sporadically infected humans as dead-end hosts. In 2009 the A/H1N1 virus acquired the capacity to spread efficiently by human to human transmission. The novel A/H1N1 influenza virus has struck thousands of people in more than 70 countries and killed more than 140, representing a public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 12 publications
3
105
0
Order By: Relevance
“…According to the ISM theory, the peak frequencies of IS of a protein sequence reflect its biological or biochemical functions. The ISM was successfully applied to quantify the effects of HA mutations on the receptor binding preference in [7,21,22]. …”
Section: Informational Spectrum Methodsmentioning
confidence: 99%
“…According to the ISM theory, the peak frequencies of IS of a protein sequence reflect its biological or biochemical functions. The ISM was successfully applied to quantify the effects of HA mutations on the receptor binding preference in [7,21,22]. …”
Section: Informational Spectrum Methodsmentioning
confidence: 99%
“…In [12,13] the same research group applied the ISM to investigate the interaction between HA and its receptors. Their findings showed that HA1 of different flu subtypes encodes one highly conserved domain that might be determinants of HA binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…The ISM was successfully applied to quantify the effects of HA mutations on the receptor binding preference in [10] and reveal the change of receptor binding selection caused by the mutations identified in [28] and [12]. Table 1 shows several common IS frequencies identified in [12,13]. It was observed in [11] that some of the influenza strains displayed dual HA receptor binding preference.…”
Section: Informational Spectrum Methodsmentioning
confidence: 99%
“…According to the ISM theory, the peak frequencies of IS of a protein sequence reflect its biological or biochemical functions. The ISM was successfully applied to quantify the effects of HA mutations on the receptor binding preference in [10] and reveal the change of receptor binding selection caused by the mutations identified in [28] and [12]. Table 1 shows several common IS frequencies identified in [12,13].…”
Section: Informational Spectrum Methodsmentioning
confidence: 99%
See 1 more Smart Citation